THE COHERENCE BETWEEN THE TEACHING PLOT WRITTEN IN LESSON PLAN WITH THE IMPLEMENTATION IN THE CLASSROOM OF JAPANESE SUBJECT - Musdalifah Yuliati Putri; Yuyun Rosliyah; Andy Moorad Oesman (Universitas Negeri Semarang, 2015)
To achieve a learning goal, in the teaching learning activity there is a component that must interact one another. Those components are lesson material, teaching learning activity, media and evaluation. Therefore, the teacher must plan a teaching plot in the lesson plan. There are many things causing the learning goal was not achieved. One of them is the teaching plot that is not coherence with the implementation in the classroom. As what happen in the Japanese subject in SMA N 14 Semarang. According to the researcher’s observation which is conducted during PPL there are 3 of 38 students that were able to confirm or able to use the sentence pattern that was taught. In the introductory study, the teaching plot written in lesson plan was coherence with the teaching goal. Based on the problems above the researcher conducted a study in the coherence between the teaching plot written in the lesson plan and in the implementation in a classroom. This study was aimed to know the coherence between the teaching plot written in the lesson plan and in the implemetation in the classroom for Japanese subject in SMA N 14 Semarang. This study was a descriptive qualitative study. The technique of data collection was using documentation and observation. The observation was conducted by observing and equipped with the observation sheet in a form of checklist. The observation was done in three meetings in class XI IS 2. However, in the implementation it can be seen from the analysis result of this study about the coherence of the teaching plot consisted of three categories which is coherence, coherence with the note, and incoherence. The coheerence step is step which explained the learning goal, basic training, closing. The activity which is coherence with the note step is the greeting, drill, conclusion. The activity which is incoherence is the activity in the step of giving motivation, games, training application, and reflecting of the activity.